Penerapan Sistem Pengarsipan Digital di Sekolah Untuk Siswa SMK Garuda Nusantara - Arwan Sulaeman, Asep; Fauziah, Sifa; Triwibowo, Edi; Soejarminto, Yos (VIDHEAS: Jurnal Nasional Abdimas Multidisiplin, 2025)
The implementation of a digital archiving system in schools is an urgent need in the digital era, particularly in improving the efficiency of data and document management. This activity aims to introduce and train Garuda Nusantara Vocational High School students in digital archive management, replacing the still-widely used conventional methods. The methods used in this activity include theoretical training, hands-on practice using digital archiving applications, and evaluation of student understanding through project assignments. The results of the activity indicate an increase in students' understanding of digital archiving concepts and practices, as well as their ability to use applications to store, manage, and search for documents effectively. The implementation of this system is expected to not only improve students' information technology skills but also support more orderly and efficient school administration. This activity is the first step in establishing a digital work culture in vocational high schools. Keywords: digital archiving, document management, information technology, vocational high schools, digital literacy.